1988
DOI: 10.1177/096032718800700607
|View full text |Cite
|
Sign up to set email alerts
|

A Signal Assay for the Detection of Genotoxic Compounds: Application on the Urines of Cancer Patients on Chemotherapy and of Nurses Handling Cytotoxic Drugs

Abstract: 1 The excretion of thioethers was determined in the urine of nurses handling cytotoxic drugs (n = 10) and cancer patients under chemotherapy (n = 32). 2 An occupational non-exposed group served as control ( n = 28). 3 We found no association between the handling of cytotoxic drugs and occupational exposure of nurses. Cancer patients under chemotherapy showed abnormally high values of thioethers, while urinary thioether concentration was, consistently, rather low in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…It is evident that exposure to the effects of CD increases unless proper measures are taken. There are many studies showing that the cytotoxic effect is increased by frequent exposure to the secretions and metabolic products of patients 2,8,9,15,25,32 . A study supporting this has been performed by Burgaz et al .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It is evident that exposure to the effects of CD increases unless proper measures are taken. There are many studies showing that the cytotoxic effect is increased by frequent exposure to the secretions and metabolic products of patients 2,8,9,15,25,32 . A study supporting this has been performed by Burgaz et al .…”
Section: Discussionmentioning
confidence: 93%
“…Twenty‐six % of nurses were pointed out that pregnant or breastfeeding staff administered CD in their clinics. Pregnant in their first trimester may experience spontaneous abortion and also chronic exposure to the CD may increase the risk of a child being born with congenital malformations 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Sasaki et al reported increased levels of DNA damage as detected by the comet assay in Japanese nurses handling antineoplastic drugs 11) . Previous studies in Turkish nurses handling antineoplastic drugs reported potential risk [12][13][14] . In the present study, antineoplastic drug handlers were using gloves and masks during the preparation of the drugs under a vertical flow safety cabinet for the last two years.…”
Section: Discussionmentioning
confidence: 99%
“…In an evaluation of excretion of thioethers in the urine of nurses handling cytotoxic drugs, the conclusion was reached that nurses exposed did not seem to absorb significant quantities of the drugs that they mixed and administered (Burgaz et al 1988).…”
Section: Urinary Mutagensmentioning
confidence: 99%